Analysis and Design of ADRC for the LCC-LCC WPT System - Wencong Huang; Wentao Lin; Peng Gao; Yufang Chang (IEEE Access)
This paper analyzes the dynamic characteristics of wireless power transfer systems based on LCC-LCC topology. By controlling the input current of the primary compensation network, the Active Disturbance Rejection Control (ADRC) Algorithm is used to realize the voltage output of the secondary compensation network indirectly, which improves the dynamic response of load voltage and anti-interference ability. Firstly, the small signal model of the system is obtained by using the generalized state-space average method. On this basis, the transient characteristics of the Wireless Power Transfer (WPT) system are analyzed and the consistency of the transient performance of the primary current and the secondary voltage is demonstrated. Secondly, the Active Disturbance Rejection Control (ADRC) strategy based on the primary side current of the Wireless Power Transfer (WPT) system is proposed and the parameter calculation rules of the controller are given. Finally, an experimental platform was built to demonstrate the theoretical analysis. The experimental result demonstrated that the proposed Active Disturbance Rejection Control (ADRC) strategy can achieve a stable output of load voltage with the response time of about 1.61ms and the voltage fluctuation of about 2V.